PENGARUH PENGUASAAN KOSAKATA BAHASA INGGRIS DAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS BAHASA INGGRIS MAHASISWA PRODI PERBANKAN DAN KEUANGAN POLITEKNIK NEGERI MEDAN TA 2012/2013 - Raina Rosanti; Budi Indra Syahdewa; Siti Asnida Nofianna; Ratna Dewi (Cross-border, 2023)
This research aims to determine the effect of English vocabulary mastery on the ability to read and understand English texts of Medan State Polytechnic Banking and Finance Study Program students for the 2012/2013 academic year who received Class Action research and those who did not receive Class Action research. The type of data collected is qualitative data with data collection tools (instruments) used in this research, namely English vocabulary tests and English text reading comprehension tests. Respondents were taken as many as 40 students. This research uses descriptive qualitative analysis techniques. The results of the research showed that there is an influence of mastery of English vocabulary on the ability to understand English texts of Medan State Polytechnic Banking and Finance Study Program students for the 2012-2013 year who received class action research compared to those who did not receive class action research.